The impact for leadership, training and development and job security factors on employee retention at aviation MRO company - Zulhilmi Masrur, A Zaini (2025)
At an aviation MRO company located in Subang Airport, this study assesses the influence of leadership, training & development, and job security on employee retention. A quantitative methodology is implemented in the investigation, which relies on employee surveys to accumulate data. A correlation and regression analysis were conducted on the data using SPSS version 29. According to the findings, employee retention is significantly and positively influenced by leadership. However, there is a negligible negative correlation between training & development and employee retention, while job security exhibits a faint positive correlation. Therefore, leadership is more critical in retaining employees than the other two factors. The results of this investigation indicate that organizations ought to prioritize effective leadership in order to enhance employee retention. These discoveries can assist aviation industry HR and management in making more informed decisions regarding employee retention